Evaluation of the Chemical Quality of Based Rations Guinea Grass (Panicum maximum) through Combination of Different Swamp Forages - Riswandi Riswandi; Muhakka Muhakka; Agus Wijaya; Afnur Imsya; Desi Kurnia; Cempaka Kirana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Swamp forage has the potential as an alternative feed for ruminants. This study aimed  to evaluate the chemical quality of Guinea grass (Panicum maximum) based rations through a combination of different types of swamp forage. This research was conducted for 3 months at the Animal Feed Nutrition Laboratory, Faculty of Agriculture, Sriwijaya University. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments consisted of R0 (70% Guinea grass + 30% Concentrate), R1 (40% Guinea grass + 30% water mimosa + 30% Concentrate), R2 (40% Guinea grass + 30% giant molesta + 30% Concentrate), R3 (40% Guinea grass + 30% water chestnut + 30% Concentrate). The variables observed were dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CF), extract ether (EE), tannin and saponins. The results showed that the treatment had a significant effect (P < 0.05) on the content of DM, OM, CP, CF, Tannins and Saponins, while the extract ether content had no significant effect (P > 0.05). Furthermore, highest DM (82.45%), OM (76.96%) and CP (16.35% were obtained in R1, CF (22.34%) in R0. Tannin best concentration (1.09%) in R3 and saponins (2.16%) in R1. The conclusion of this study showed that the combination of 40% Guinea grass + 30% water mimosa + 30% concentrate could improve the chemical quality of the ration.